DFT-Based Molecular Analysis of Imidazole Derivatives as Additives to Enhance Ionic Conductivity in Polymer Electrolyte Membranes - Marvin Pasaribu; Mokhamat Ariefin; Sun Theo Constan Lotebulo Ndruru; Ferdinand Hidayat; Multazam (Universitas PGRI Madiun, 2025)
The demand for efficient and stable lithium-ion batteries has driven research on advanced polymer electrolyte membranes (PEM) with improved ionic conductivity. This study investigated imidazole and its derivatives as additives in PEM to enhance battery performance. Using Density Functional Theory (DFT) with the def2-TZVP basis set, key quantum parameters such as HOMO-LUMO energies, energy gap (?Egap), electronegativity (?), softness (?), electron transfer fraction (?N), and net electrophilicity (??) were analyzed. Results showed that imidazole derivatives with electron-withdrawing groups, like acrylate and tosyl, had lower ELUMO and smaller ?Egap, improving lithium ion (Li?) interactions and mobility within the polymer matrix. Additionally, compounds with high ? and ?, such as BTIM and BZIM, enhanced ion stabilization and transport, leading to better electrolyte performance. Thus, modifying imidazole structures through specific substitutions is a promising approach to optimize PEM, supporting the development of more efficient and stable lithium-ion batteries.